Contrasting patterns of population structure at large and fine geographical scales in a migratory avian disturbance specialist of braided river ecosystems. Issue 1 (1st October 2019) - Schlesselmann, Ann‐Kathrin V.; Dussex, Nicolas; Cooper, Jamie; Monks, Joanne M.; O'Donnell, Colin F. J.; Robertson, Bruce C.
Abstract: Aim: To understand the population structure and its potential drivers at different spatial scales in a migratory bird, the black‐fronted tern ( Chlidonias albostriatus ), a specialist of the spatially and temporally dynamic environments of braided rivers. Location: New Zealand. Methods: We used a three‐pronged approach based on 17 microsatellites, two mitochondrial loci (cytochrome b/control region) and phenotypic data (head‐bill length, bill depth, wing length, weight). We determined large‐scale genetic structure throughout the whole breeding range (approx. 150, 000 km 2 ), calculated genetic divergence of breeding colonies and tested for isolation‐by‐distance between colonies. We investigated the level of fine‐scale genetic structure based on spatial autocorrelation analyses and assessed the presence of a body size cline based on phenotypic data. Lastly, we compared phenotypic divergence ( P ST ) and the level of divergence by genetic drift ( F ST ) among breeding colonies to test for underlying mechanisms of population differentiation. Results: Nuclear and mitochondrial DNA showed that across their range black‐fronted terns were effectively panmictic, with low genetic divergence between breeding colonies overall and no isolation‐by‐distance. However, at fine geographical scales black‐fronted terns accrued significant genetic structure for distances up to 75 km, primarily driven by males, indicating more frequent female dispersal. Furthermore, a phenotypic cline in accordance with Bergmann's rule was evident. P ST exceeded F ST in three traits, suggestive of local adaptation. Main conclusions: Significant fine‐scale structure can be present in highly mobile, specialist species while not affecting spatial structures at larger scales. Hence, methodologies applied to both whole landscapes and local scales are important to appropriately estimate connectivity in dynamic metapopulations and investigate the processes behind connectivity. Conservation management will need to include protecting currently uninhabited patches to facilitate natural colonization of suitable habitat. For black‐fronted terns, managing whole catchments throughout the entire breeding range would be preferable to managing single patches.